The true image: gravestone art and the culture of Scotch Irish settlers in the Pennsylvania and Carolina backcountry - Patterson, Daniel Watkins (The Richard Hampton Jenrette series in architecture and the decorative arts, 2012)
The immigrant craftsmen in Pennsylvania -- The stonecutters' world in the Carolinas -- The Bigham workshop and nearby Scotch Irish stonecutters -- Reading Scotch Irish emblems -- Seeing Scotch Irish inscriptions -- The Scotch Irish in the light of legends -- Reflections on the stonecutters' world -- The Scotch Irish in slave economy and landgrab